Analisis Spasial Tikus Positif Leptospira Patogenik dan Jenis Habitatnya di Provinsi Papua Barat - Arief Nugroho; Ika Martiningsih; Nur Hidayati; Muhidin Muhidin; Ristiyanto Ristiyanto (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2019)
Leptospirosis is a disease caused by pathogenic Leptospira and is still a health problem in the community. Until now, West Papua Province has not reported any cases of leptospirosis. This study aims to examine whether there is a grouping pattern of Leptospira harboring rats and identify the habitat types of positive rat Leptospira. This research was descriptive observational research using a cross-sectional approach. Research locations are in Manokwari, Fakfak, and Raja Ampat districts in West Papua Province. The catching of rats was carried out in locations of forest ecosystem settlements, near forest settlements, non-forested far from settlements, non-forests near settlements, coastal remote settlements, and beaches near settlements. Leptospira in rats was detected by examination of Polymerase Chain Reaction (PCR) and Microscopic Agglutination Test (MAT). The results showed 278 rats were caught. The number of Leptospira positive rats in three districts by PCR was 34 (12.2%) and MAT were 13 (4.7%). Leptospira positive habitat types were settlements, yards, and secondary forests. The SaTScan results were obtained by six positive Leptospira rat clusters. There were no significant results which showed that no spread of Leptospira in the clusters. The presence of Leptospira in rats should be a warning for leptospirosis transmission risk at the study site.